The Role of Workplace Diversity and Leadership Empowerment in Driving Organizational Innovation - Aleeza Ghafoor (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2024)
This study investigates the effect of workplace diversity and leadership empowerment on organizational innovation. The primary objective is to explore how a diverse workforce and empowered leadership practices contribute to fostering innovative ideas, processes, and solutions within organizations. Additionally, the study examines the mediating role of organizational culture in enhancing the relationship between diversity, leadership empowerment, and innovation. Lastly, it evaluates the moderating effect of employee collaboration on these dynamics. The research adopts a quantitative methodology, grounded in a positivist research philosophy, to provide an objective and statistical understanding of the relationships among the variables. The study’s population comprises employees from multinational corporations, with a sample size of 300 participants selected using a convenience sampling technique. The study also identifies employee collaboration as a critical moderator that strengthens these relationships, emphasizing the importance of teamwork in achieving innovative outcomes. This research highlights the pivotal roles of workplace diversity and leadership empowerment in driving innovation and provides practical insights for organizations seeking to enhance their innovative capacity